Penguatan Fungsi Keluarga dan Self Care Behaviour Lansia Hipertensi dan Diabetes Melitus melalui Posdaya - Adila Solida; Rumita Ena Sari; Evy Wisudariani; Rizalia Wardiah; Fajrina Hidayati (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Hypertension and diabetes mellitus, which many elderly suffer from, are a significant problem in Indonesia because they pose a risk of serious complications and even death. At the Olak Kemang Community Health Center, the incidence of hypertension and diabetes mellitus in the elderly has increased. However, the scope of elderly people's active participation in various hypertension and diabetes mellitus management programs is still low. Based on the results of the team's research and initial observations, it is known that the main cause of this problem is a lack of family support and limited knowledge about the efforts that families must make in managing illnesses in the elderly. This situation indicates weak family functioning which has an impact on health. This community service activity aims to strengthen family functions and self-care behavior for elderly people with hypertension and diabetes mellitus in the work area of the Olak Kemang Community Health Center through the implementation of Posdaya (Family Empowerment Post). Posdaya activities include counseling about family functions, developing family skills to manage hypertension and diabetes mellitus in the elderly, as well as assisting families to be able to access various application-based health services for the elderly and families. The activity was attended by 20 elderly people and their families. The results of the activity showed that 80% of participants experienced increased knowledge. In addition, participants provided statements of attitude to improve family function and implement self-care behavior for elderly people with hypertension and diabetes mellitus.